Carbon ion-beam-induced modification in structural and electrical properties of ZnO nanowires - Iqbal, Javed; Tabassum, H.; Ahmad, Ishaq; Jan, Tariq; C.F., Dee; Madhuku, M.; Umar, A.A.; Ahmad, N. (Universiti Kebangsaan Malaysia, 2014)
Zinc oxide nanowires (ZnO NWs) have an efficacious place in nanoworld due to their tremendous properties and applications. In the present work, structural and electrical properties of ZnO NWs have been modified by carbon (C) ions- beam irradiation. With ion-beam energy of 0.8MeV, the physical behaviors of NWs have been studied under different doses from 1×1012 to 1×1014 ions/cm2. The microstructural and Raman spectroscopy studies showed that the wurtzite crystal structure of the ZnO NWs has been changed into disordered amorphous one under high C ion doses. Whereas, the XRD results showed that Zn nanoparticles are fabricated at high C ion-beam irradiation on ZnO NWs. Scanning electron microscopy (SEM) depicts the formation of cross junctions and parallel junctions between ZnO NWs after C ion irradiation. DC conductivity measurements have confirmed that the conductivity of NWs decreases with increase in C ion doses. It is concluded that the lattice defects significantly contribute to decrease in the conductivity of ZnO NWs.